Preparation, Characterization and Optimization of Carvedilol Loaded Chitosan Nanoparticles by Applying Taguchi Orthogonal Array Design - Sharma, Rajesh (Asian Journal of Pharmaceutics (AJP), 2017)
Aim: The aim of the study was to develop and optimize carvedilol (CAR) loaded chitosan (CS) nanoparticles (NPs) to enhance its oral bioavailability and comparing it with marketed tablets. Materials and Methods: The NPs were prepared by ionic gelation technique and evaluated for particle size, zeta potential (ZP), entrapment efficiency, in vitro release kinetics, and stability profile. Results and Discussion: The results indicated stable CAR-CS NPs with the value of ZP to be +32 mV Â± 2 mV, the small particle size of 79.23 nm and high entrapment efficiency of 72.56%. The optimization of the formulation by Taguchi orthogonal array design exhibited C3T5R11S20 as the optimized batch with CS concentration of 0.3% w/v, tripolyphosphate (TPP) concentration of 0.5% w/v, CS: TPP volume ratio of 1:1 v/v and a stirring speed of 2000 rpm. The in vitro release study revealed sustained release of drug for 72 h with 74.84% cumulative drug release. Conclusion: The promising results from the study revealed the applicability of Taguchi orthogonal array design in identifying the critical parameters in the formulation of CAR loaded CS NPs.